KNOW YOUR BANKNOTES - . Nag, S.K (Ushus Journal of Business Management, 2003)
Banknotes or currency notes are important constituent of any economy and Indian economy is no exception. Banknotes of India are security products of high symbolic value and are considered an important national feature by this sovereign country. Currency notes of this country are an expression of stability and trust in its economic power and that explains the eternal craving for more and more of it.